Effect of Competition Frequency on Strength Performance of Powerlifting Athletes. Issue 5 (May 2020) - Pearson, Joshua; Spathis, Jemima G.; van den Hoek, Daniel J.; Owen, Patrick J.; Weakley, Jonathon; Latella, Christopher
Abstract : Abstract: Pearson, J, Spathis, JG, van den Hoek, DJ, Owen, PJ, Weakley, J, and Latella, C. Effect of competition frequency on strength performance of powerlifting athletes. J Strength Cond Res 34(5): 1213–1219, 2020—Powerlifting (PL) requires athletes to achieve the highest possible "total" weight lifted across squat, bench press, and deadlift. Athletes compete multiple times per year; however, it is not well understood how often PL athletes should compete to facilitate maximal strength performance. This study investigated the effect of competition frequency on strength (relative and absolute) in PL athletes over a 12-month period. Results across all male ( n = 563, mean ± SD ; age; 28 ± 10 years, body mass; 89.3 ± 19.3 kg) and female ( n = 437, age; 31 ± 11 years, body mass; 70.1 ± 15.8 kg) PL athletes were collated. Total competition scores were used to calculate absolute and relative strength for each competition. Linear mixed models with random effects, and effect sizes ± 95% confidence intervals compared competition frequency and total score for (a) all, (b) male, and (c) female competition entries, respectively. The association between total score at each competition was assessed with Pearson's correlation coefficient for the same independent variables. Results demonstrate greater absolute strength at competition 2 for all athletes (5.1%: p = 0.043: d = 0.16) and males (2.9%: p = 0.049: d = 0.15). For females, absolute strength was greater at competition 5 compared to 1 (12.0%: p = 0.001: d = 0.65) and 2 (9.6%: p = 0.007: d = 0.50). Weak positive correlations for relative strength and number of times competed for males were evident between competitions 1 to 4 ( r 2 = 0.070–0.085, p = 0.003–0.043). For females, 3 competitions weakly correlated with absolute strength ( r 2 = 0.106, p = 0.016). PL athletes who compete multiple times per year are more likely to achieve higher totals; however, there is an upper limit to the number of competitions (4 per year) that seem to allow a performance increase.